Jean-Luc Marion y la reducción a y de la llamada - Porcel Moreno, Manuel (Pontificia Universidad Católica del Perú, 2024)
In his essay Réduction et donation, the French philosopher proposes a new principle –“autant de réduction, autant de donation”–, from which he will propose a third reduction in the field of phenomenology. The intent of this paper is to show how this principle points out that reduction, increasingly radicalized, not only reduces in a restrictive sense but rather opens or widens the horizon of donation, since it allows us to penetrate more and more into the very fact of donation as such. Thus, we will conclude that after the phenomenological-transcendental reduction and the ontological-existential reduction, the reduction to and from the call is exercised, which underlies as the fundamental scheme of the two previous reductions. This will be conceived as the original structure of the donation.

El filósofo francés en su obra Réduction et donation nos propone un nuevo principio –“autant de réduction, autant de donation”–, a partir del cual planteará una tercera reducción en el campo de la fenomenología. La pretensión de este artículo consiste en mostrar cómo este principio señala que la reducción, cada vez más radicalizada, no solo reduce en un sentido restrictivo, sino, más bien, abre o amplía el horizonte de la donación, puesto que permite penetrar cada vez más en el hecho mismo de la donación como tal. De este modo, concluiremos que tras la reducción fenomenológica-transcendental y la reducción ontológica-existencial se ejerce la reducción a y de la llamada, la cual subyace como el esquema fundamental de las dos reducciones anteriores. Esta será concebida como la estructura originaria de la donación.
Jean-Luc Marion and the Reduction to and of the Call
Keywords: Transcendental ego; Dasein; Reduction to and from the call; Donation; Challenged; Yo trascendental; Dasein; Reducción a y de la llamada; Donación; Interpelado; https://purl.org/pe-repo/ocde/ford#6.03.01